Factors That Affect Taxpayer's Will To Follow Tax Amnesty Program - Zaenal Afifi, Nanik Ermawati, (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The purpose of this study is to analyze the factors that influence the willingness of taxpayers to take part in tax amnesty. The type of research used in this research is explanatory research which is testing hypotheses. The population used is an individual taxpayer at KPP Pratama Pati. The sampling technique used was convenience sampling method. The test equipment used is the Structural Equation Model (SEM) approach using an alternative method of Partial Least Square (PLS). The results showed that 1). the perception of taxpayers regarding tax amnesty does not affect the willingness of taxpayers to follow tax amnesty, 2). Taxpayer perception regarding tax amnesty does not affect the awareness of taxpayers, 3). The perception of taxpayers regarding tax amnesty does not affect tax knowledge, 4). The awareness of taxpayers influences the willingness of taxpayers, following tax amnesty, 5). Knowledge of taxation does not affect the willingness of taxpayers to take tax amnesty.Ã‚Â